REDESAIN SISTEM INFORMASI SEKOLAH MA AL-ISTIQOMAH CARINGIN BERBASIS WEB MENGGUNAKAN LARAVEL DAN VUE.JS DENGAN METODE AGILE SCRUM - Ryandra Putra; Gugun Gunadi; Aisah Rini Susanti; Setyono Setyono (Simtek : jurnal sistem informasi dan teknik komputer, 2026)
School information systems have been widely used to improve the effectiveness of educational information management and administrative processes. MA Al-Istiqomah Caringin has previously utilized a website as an information medium; however, it still has limitations in administrative features, lacks an integrated online registration system, and presents a less interactive and appealing user interface. This study aims to develop a web-based school administration system using Laravel as the backend and Vue.js as the frontend. The Agile Scrum method was applied to support an iterative and flexible development process. The results of this study indicate that the developed system is capable of providing administrative management features, tuition fee (SPP) payment status tracking, and an online registration system with QR Code-based email verification. The resulting system is more dynamic, responsive, and effective in supporting administrative services as well as the school's digital promotion.